2017
DOI: 10.1021/jacs.7b09352
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Water Accessibility of the Trimeric Membrane Anchors of the HIV-1 Envelope Spikes

Abstract: HIV-1 envelope spike (Env) is a type I membrane protein that mediates viral entry. Recent studies showed that the transmembrane domain (TMD) of the Env forms a trimer in lipid bilayer and that disruption of the TMD could significantly alter the antigenic properties of the Env. The TMD structure has several peculiar features that remain difficult to explain. One is the presence of an arginine R696 (three in the trimer) in the middle of the TM helix. Additionally, the N- and C-terminal halves of the TM helix for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 30 publications
5
31
0
Order By: Relevance
“…To gain a greater understanding of the interplay between the HIV gp41 TMD and a viral membrane, we performed extensive MD simulations of the TMD trimer in a heterogeneous, asymmetric membrane. While it has been recently observed that a highly conserved arginine residue (R696) is a mediator of water exchange in the TMD trimer (24), we sought to further analyze the dynamics and movement of water, and potentially ions, into the trimer core. Additionally, we sought to provide further insight into the role of the highly conserved, positively charged residues that sit at the membrane-water interfaced based on the recent NMR structure (PDB ID: 5JYN).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To gain a greater understanding of the interplay between the HIV gp41 TMD and a viral membrane, we performed extensive MD simulations of the TMD trimer in a heterogeneous, asymmetric membrane. While it has been recently observed that a highly conserved arginine residue (R696) is a mediator of water exchange in the TMD trimer (24), we sought to further analyze the dynamics and movement of water, and potentially ions, into the trimer core. Additionally, we sought to provide further insight into the role of the highly conserved, positively charged residues that sit at the membrane-water interfaced based on the recent NMR structure (PDB ID: 5JYN).…”
Section: Resultsmentioning
confidence: 99%
“…The highly conserved gp41 TMD transmembrane domain (TMD) of Env ( Figure 1) is anchored in a cholesterol-rich lipid bilayer (22) that is flanked by the membrane proximal external region (MPER) on the exofacial leaflet and the cytoplasmic tail (CT) on the cytofacial leaflet. In the prefusion state, either one (23) or three (21,24,25) single-pass α-helices span the membrane ( Figure 1A). Previous studies have proposed that either oligomeric contacts (21,24) or head group snorkeling (23) stabilizes an internal arginine, R696, which is buried in the membrane (21).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations